Fashioning the Self: Reinvention as Depicted in Jennifer Down's "Bodies of Light" - Syofyan, Donny (Jurnal Ceteris Paribus, 2024)
A recent study has identified the key factors that contribute to the themes explored in Jennifer Down's award-winning novel, Bodies of Light. The book has received literary criticism for its portrayal of human bondage, vulnerability, and social distinction, making these themes the primary focus of the study. By delving into the underlying themes and attributions within the novel, this analysis has provided valuable insights into the story. Notably, the study has shed light on the power dynamics between male characters, and the protagonist's struggle with pain, emotional trauma, and poignancy. Furthermore, previous research has highlighted the connections between the novel's exploration of existential crisis and identity. Keywords: Human Bondage, Emotional Investment, Vulnerability, Childhood Grief, Emotional Instability.